DIGITAL HUMANITARIANISM: MYTHS AND REALITIES - Madianou, Mirca (AoIR Selected Papers of Internet Research, 2016)
The 2013 World Disasters Report uses the term ’humanitarian technology’ to refer to the empowering nature of digital technologies such as mobile phones and social media for disaster recovery. It is claimed that interactive technologies enable affected communities to participate in their own recovery, respond to their own problems and ‘make their voices heard.’ Digital communication technologies are welcomed for their potential to catalyze a ‘power-shift’ in humanitarianism by building feedback structures that empower local communities to hold humanitarian and government agencies into account. Indeed a new era of humanitarianism is proclaimed which is driven by digital developments (Meier, 2015; UN OCHA, 2012). Despite the enthusiasm regarding the role of digital technologies as tools for humanitarian relief there is little evidence to support the above claims. My paper unpacks some of the myths surrounding digital technologies for disaster recovery and humanitarian aid. Rather than assuming the usefulness, inherently progressive or democratizing nature of communication technologies, I will reflect on the affordances of digital media, their actual uses by disaster affected people and how these contribute to key processes of humanitarian practice such as and ‘accountability’.